1984
DOI: 10.1007/bf01973849
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in histamine and collagen induced in chick embryos by aminoguanidine and 48/80

Abstract: The effects of aminoguanidine (a histamine inhibitor) and 48/80 (a histamine liberator) on the levels of histamine, soluble collagen fraction and total collagen in the chick embryos were studied. Histamine content in bones (tibia and femur) and skin markedly increased in the embryos treated with aminoguanidine. Aminoguanidine treatment was followed by a decrease of total collagen and an increase of soluble collagen fraction both in bones and skin. 48/80 did not change the histamine level in the bones but decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Also, similarities have been found between mast cells and both natural killer and suppressor T cells (21-23). Furthermore, there is evidence that mast cell degranulation, triggered by compound 48/80 or Polymixin B, stimulates fibroblast proliferation and collagen deposition (24,25). When immune responding animal strains are shown to have plentiful mast cells, it is difficult to determine whether mast cells lead to immunoresponsiveness or vice versa.…”
Section: Resultsmentioning
confidence: 98%
“…Also, similarities have been found between mast cells and both natural killer and suppressor T cells (21-23). Furthermore, there is evidence that mast cell degranulation, triggered by compound 48/80 or Polymixin B, stimulates fibroblast proliferation and collagen deposition (24,25). When immune responding animal strains are shown to have plentiful mast cells, it is difficult to determine whether mast cells lead to immunoresponsiveness or vice versa.…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, in addition to being found at sites of collagen accumulation a number of observations have been made that corroborate their potential role in the pathogenesis of scleroderma. Mast cell degranulation in vitro is associated with fibroblast stimulation and collagen production.21 22 Furthermore, mast cell granules are intemalised by fibroblasts,10 demonstrating that an interaction between the two cell types may exist.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of these experiments was the original observations by Baylin et al (l975), who showed that the diamine oxidase inhibitor aminoguanidine reduces nitrogen excretion in cancer cachexia and promoted tissue growth in laboratory rats. Studies by various other groups have also shown that aminoguanidine has other novel pharmacological effects (Moulinoux et al 1977;Dabrowski & Szczepanowska 1984;Khatami et a1 1988;Tamura et a1 1989;Nicholls & Mandel 1989). However, there is a paucity of data on its possible effects on plasma analytes.…”
Section: Discussionmentioning
confidence: 98%
“…It has the ability to inhibit the non-enzymatic glycosylation of serum albumin and advanced glycosylation end-products in renal basement membranes (Khatami et al 1988;Nicholls & Mandel 1989). Moreover, aminoguanidine also increases the proportion of soluble collagens and diminishes total collagens in skin and bones (Dabrowski & Szczepanowska 1984). Other studies have shown that aminoguanidine can alter hepatic and blood levels of histamine after partial hepatectomy (Moulinoux et a1 1977).…”
mentioning
confidence: 91%